Leadership development for future leaders in a VUCA world - Defining the population and reimagining capability building - Jazeel, Sara (Cranfield University, 2025)
Purpose - The purpose of this thesis is to first provide definitional clarity for the term 'emerging leader' and second to identify the necessary VUCA (Volatile, Uncertain, Complex, Ambiguous) specific competencies that should be focused on in leadership development for this specific demographic. Design/Methodology/Approach – A three-pronged approach was taken, first with a modified systematic literature review (SLR) on emerging leadership development and VUCA leadership development, second was a market research review of key emerging leader and VUCA leadership development programmes, and third, primary research utilising a qualitative (interview-based) methodology grounded in interpretative phenomenological analysis (IPA) for data collection and analysis. The participants formed two groups: Group A – Potential emerging leaders (T1), and Group B – Professionals with experience in human resources, talent management, and career management (T2 and T3). These groups allowed for a multi-stakeholder view on the research questions. Findings – Through the modified SLR, the thesis identified a definitional void for 'emerging leaders' across both literature and practice. The market research review supported the findings of the SLR, while showcasing a lack of programmes that cater to Emerging Leaders in a VUCA world. The primary research found that participants predominantly demonstrated 'reluctant leadership' arising through external recognition rather than self-selection or active ambition, and interpersonal competencies emerged as foundational to VUCA navigation, challenging the existing literature's cognitive emphasis. Theoretical Contributions – A. Definitional clarity for the term ‘emerging leader’ which has been a neglected concept in terms of definition. B. Developing a competency framework for leadership development and assessment in VUCA contexts specific to emerging leaders, which extends on existing findings. Practical Implications - Organisations should redesign talent identification beyond self-nomination to recognise “reluctant leadership” and shift to stage-based rather than tenure-based development. Recruitment and promotion criteria should prioritise interpersonal and adaptive competencies alongside more traditional technical skills. This involves developing integrated competency frameworks that address the specific capabilities required in a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment. Value - The research provides an empirically grounded working definition of 'emerging leaders'. It establishes interpersonal capabilities as perhaps foundational to VUCA leadership rather than supplementary, introduces 'learning through complexity' as a meta-competency, and demonstrates how organisational barriers could systematically undermine development effectiveness.
Keywords: emerging leader; definitional ambiguity; VUCA competencies; competency frameworks; emerging leader development